Extended Multilocus Sequence Analysis to Describe the Global Population Structure of the Genus Brucella: Phylogeography and Relationship to Biovars - Whatmore, Adrian M.; Koylass, Mark S.; Muchowski, Jakub; Edwards-Smallbone, James; Gopaul, Krishna K.; Perrett, Lorraine L. (Frontiers in Microbiology, 2016)
An extended multilocus sequence analysis (MLSA) scheme applicable to the Brucella, an expanding genus that includes zoonotic pathogens that severely impact animal and human health across large parts of the globe, was developed. The scheme, which extends a previously described 9 locus scheme by examining sequences at 21 independent genetic loci in order to increase discriminatory power, was applied to a globally and temporally diverse collection of over 500 isolates representing all twelve known Brucella species providing an expanded and detailed understanding of the population genetic structure of the group. Over 100 sequence types (STs) were identified and analysis of data provided insights into both the global evolutionary history of the genus, suggesting that early emerging B. abortus lineages might be confined to Africa while some later lineages have spread worldwide, and further evidence of the existence of lineages with restricted host or geographical ranges. The relationship between biovar, long used as a crude epidemiological marker, and genotype was also examined and showed decreasing congruence in the order B. suis > B. abortus > B. melitensis. Both the previously described 9 locus scheme and the extended 21 locus scheme have been made available at http://pubmlst.org/brucella/ to allow the community to interrogate existing data and compare with newly generated data.